Shakespeare and modernity : early modern to millennium - Grady, Hugh (Accents on Shakespeare., 2000)
This in-depth collection of essays traces the changing reception of Shakespeare over the past four hundred years, during which time Shakespeare has variously been seen as the last great exponent of pre-modern Western culture, a crucial inaugurator of modernity, and a prophet of postmodernity. This fresh look at Shakespeare's plays is an important contribution to the revival of the idea of 'modernity' and how we periodise ourselves, and Shakespeare, at the beginning of a new millennium.